IDEOLOGI JOKOWI DALAM KEMENANGAN PEMILU 2019: MODEN DAN KESATUAN DALAM KEPELBAGAIAN TERHADAP INDONESIA - Tawakkal, Alamsyah; Awang Pawi, Awang Azman; Kaur, Surinderpal (JURNAL MELAYU SEDUNIA, 2019)
Jokowi is the phenomenal president of Indonesia and a well-known figure since his first time as the mayor, governor, and president of Indonesia in two periods from the year 2014 to 2019 and 2019 to 2024. Much of the focus surrounding the ideology of Jokowi’s victory in 2019 to lead Indonesia to a modern country. This article aims to analyze Jokowi’s ideology in administering the Republic of Indonesia by using the theory of William. Twelve Jokowi’s presidential campaign speeches during his election in 2019 are analyzed, focusing on his campaign in Java, Sumatera, Kalimantan, and Sulawesi. The data were retrieved from YouTube and LiveTV during the period of the campaign. The analysis was in qualitative and content analysis. This article showed Jokowi’s ideology in developing Indonesia with modern and unity of diversity as the prominent goal to compete and play a role to reinforce Indonesia in the region. Several recommendations are highlighted related to Jokowi’s ideology to ensure and convince people to administer Indonesia with a strengthened in the human resource without discriminations and can lead citizens who are different in ethnics, race, religion, and culture.